Evaluation of Prostate specific antigen levels and its correlation with histopathological findings - Sujata Pudasaini (Journal of Pathology of Nepal, 2019)
Background: Prostate specific antigen is a tumor marker though is expressed by both normal and neoplastic prostate tissue. The absolute value of Prostate specific antigen is useful for determining the extent of prostate cancer and its treatment. Prostate specific antigen also increases in cases like Benign Prostatic Hyperplasia and prostatitis. The availability of Prostate specific antigen as a marker has encouraged its use to diagnose both cancer and cancer recurrences.